Brush of angel's wings [large type] - Reid, Ruth, 1963- (Reid, Ruth, 1963- Heaven on earth, 2012)
Rachel Hartzler, the youngest and last unmarried sister of four Amish girls, and Jordan Engles, her father's new hired hand, are hostile to one another at first, but angelic intervention draws them together.